Determinan Kejadian Diare di Kelurahan Tangkahan, Medan Labuhan - Alfiya Syahri; Anna Tasya Putri; Alvi Hazri Lubis; Amira Arni; Adinda Afifah; Yulia Khairina Ashar (Universitas Batanghari Jambi, 2023)
Diarrhea is the second cause of death in children under the age of 5, which is around 760,000 cases/year. In Indonesia, diarrhea affects all age groups with the most cases occurring in children under 5 years of age, which is around 16.7%. There are several factors related to the incidence of diarrhea, namely the limited supply of clean water, water contaminated with feces, lack of sanitation facilities, unhygienic disposal of feces, poor personal and environmental hygiene, and inappropriate food preparation and storage. This study aims to determine the risk factors for diarrhea that occur in the community in Tangkahan Village, Medan Labuhan in 2022. The type of research used is quantitative with descriptive analytic methods and uses a cross sectional approach. Taking respondents with the Cluster Sampling technique as many as 210 respondents. The statistical test in analyzing the research data uses the Chi-square method. The results of this study indicate that there is a relationship between unhealthy food consumption (p-value = 0.029) and the incidence of diarrhea in Tangkahan Village in 2022.